The Role of Influencers in Increasing Sales of Sharia Insurance Products in Indonesia - Anisa Bella Saragih; Nurbaiti; Fauzi Arif Lubis (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
In the rapidly evolving digital era, the marketing landscape has undergone a significant transformation, including within the financial and insurance industries. Conventional communication strategies are gradually being replaced by more adaptive approaches, such as the use of digital influencers. This study aims to explore the role of influencers in increasing the sales of Islamic insurance (takaful) products in Indonesia. Amid the fast-paced digital transformation, insurance companies face challenges in designing more effective marketing strategies to reach a broader and more relevant audience. This research employs a qualitative method with a literature review approach, analyzing and interpreting various previous studies and social phenomena related to influencer-based marketing in the Islamic insurance sector. The findings reveal that influencers play a strategic role in enhancing public interest and trust in Islamic insurance products. Credible influencers can expand marketing reach, increase audience engagement, and build stronger relationships with potential customers. These results indicate that collaboration between Islamic insurance companies and digital influencers can significantly enhance marketing communication effectiveness and strengthen product positioning in the market. Therefore, selecting the right influencer becomes a key factor in maximizing digital marketing strategies in an increasingly competitive industry.